Gypsum-cement-puzzolanic concrete for 3D CP - R. Z. Rakhimov; R. Kh. Mukhametrakhimov; A. R. Galautdinov; L. V. Ziganshina (Vestnik MGSU)
Introduction. 3D concrete printing (3DCP), carried out with concrete and mortar mixtures based on mineral binders, including hybrid mixtures, is one of the promising methods for the concrete products industry. The analysis of the current state of research in the field of development of composite materials based on gypsum-cement-pozzolanic binder for 3DCP indicates the limitations of its use due to the short setting time of gypsum, as well as low water resistance and tensile strength of products based on it, which indicates the relevance of research, aimed at developing stable compositions of gypsum-cement-pozzolanic concrete for 3DCP, with high physical, technical and optimal rheotechnological characteristics.Materials and methods. The production of specimens was carried out on construction 3D printer “AMT S-6044” produced by “SPETSAVIA” LLC. Standard methods for studying rheological properties, physical and technical properties of concrete were applied.Results. The composition of gypsum-cement-pozzolanic concrete (GCPC) in 3DCP was theoretically substantiated and experimentally determined. Rational application of concrete with binder: aggregate ratio = 1:2, sand fineness modulus of Mk 3, providing the following characteristics of the control concrete composition: compressive strength — 22.1 MPa, bending strength — 4.9 MPa, average density — 1,892 kg/m3, dimensional stability 16 cm, ultimate shear stress 58.5 Pa was substantiated in 3DCP. The peculiarities of structure formation and some drawbacks of microstructure of the developed gypsum-cement-pozzolanic concrete formed by the additive manufacturing method were studied.Conclusions. Gypsum-cement-pozzolanic concretes were developed for 3DCP with an optimal ratio of components in the binder composition. The prospects for further improvement of GCPC compositions by modifying them with multifunctional complex additives were shown.